2013
DOI: 10.1093/nar/gkt055
|View full text |Cite
|
Sign up to set email alerts
|

Most RNAs regulating ribosomal protein biosynthesis in Escherichia coli are narrowly distributed to Gammaproteobacteria

Abstract: In Escherichia coli, 12 distinct RNA structures within the transcripts encoding ribosomal proteins interact with specific ribosomal proteins to allow autogenous regulation of expression from large multi-gene operons, thus coordinating ribosomal protein biosynthesis across multiple operons. However, these RNA structures are typically not represented in the RNA Families Database or annotated in genomic sequences databases, and their phylogenetic distribution is largely unknown. To investigate the extent to which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 101 publications
8
99
0
1
Order By: Relevance
“…3). The similar phylogenetic distribution has been previously found for the 5 ′ UTRs of the S10 (Allen et al 1999) and rpsA operons (Boni et al 2001;Tchufistova et al 2003), while the rpsB-tsf regulatory RNA showed more wide conservation including Psedomonadaceae (Aseev et al 2009;Fu et al 2013). The found phylogenetic similarity implies that the predicted folding of the rplY 5 ′ UTR might have biological relevance (Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…3). The similar phylogenetic distribution has been previously found for the 5 ′ UTRs of the S10 (Allen et al 1999) and rpsA operons (Boni et al 2001;Tchufistova et al 2003), while the rpsB-tsf regulatory RNA showed more wide conservation including Psedomonadaceae (Aseev et al 2009;Fu et al 2013). The found phylogenetic similarity implies that the predicted folding of the rplY 5 ′ UTR might have biological relevance (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Regulation of ribosomal protein L25 synthesis www.rnajournal.org 853 bacterial phyla has been found in a few cases (Fu et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…According to the recent study on RNA motifs regulating r-protein biosynthesis (Fu et al 2013), such universal occurrence puts the S6S18CBM motif among most widespread cis-regulatory motifs in bacterial r-protein operon leaders.…”
Section: Thementioning
confidence: 99%
“…This interaction inhibits translation initiation by occlusion of a ribosome binding site or ribosome entrapment, permitting maintenance of the balance of r-protein and rRNA levels. In Escherichia coli, there are 12 known distinct mRNA regulatory elements that control 11 r-protein operons, i.e., α, spc, S10, str, rpsT, rpsB-tsf, rspA, rpmI-rplT, rpsO, rplK-rplA, and rplJ-rplL (Fu et al 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation